Multi-Layered Non-Linear Viscoelastic Beams Subjected to Torsion at a Constant Speed: A Delamination Analysis - RIZOV, Victor; ALTENBACH, Holm (Engineering Transactions, 2022)
A non-linear mechanical model with a linear spring, a linear dashpot and a non-linear dashpot is used for studying the non-linear viscoelastic behaviour of a multi-layered inhomogeneous beam with a delamination crack. The beam with a circular cross-section is under a torsion moment that increases at a constant speed. The non-linear stress-strain-time constitutive law of the model is obtained by adding the non-linear shear strain to the strain in the linear spring and linear dashpot. Solutions of the time-dependent strain energy release rate are derived, which take into account the non-linear viscoelastic behaviour of the beam and the torsion moment rate.